A Response to Bruce Hindmarsh’s Diagnosing the Problem of Christian Immaturity: A Historical Perspective - Rhee, Helen (Journal of spiritual formation & soul care, 2025)
My response highlights two overarching crossbars to Hindmarsh’s five guiding propositions, the crossbars that engage each of those propositions as a whole. First, Christians will likely fail to mature if they fail to understand salvation as a life-long journey with a destination to reach. Salvation in much of the church history has been understood as an entire Christian life, starting in baptism and journeying toward theosis (“deification”). This notion of theosis, also expressed as Christlikeness or holiness, is the destination for Christian maturity. Second, many Christians would likely fail to mature if they failed to recognize the import of suffering in working toward Christian maturity. Since Christ’s allconsuming passion and death provides a pivotal theological and practical significance for Christians’ suffering, Christian bearing of suffering is our imitation of Christ par excellence, without which Christian maturity is improbable.